Pembuatan peta photo udara Desa Wonosari menggunakan UAV Fixed Wing - Hendra Saputra; Armada Armada (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Wonosari Village has natural resources such as agriculture, plantations and tourism. Plantation sector such as oil palm and rubber. In the tourism sector, Wonosari Village has forest areas that are wide enough to be used as an attraction for the village, such as natural forests, outbound places, as campsites, and reservoirs/lakes. To maximize this potential, it takes careful and comprehensive planning. Large-scale aerial images maps are a solution to serve as guidelines in determining and policymakers. In these activities, the method used is the use of UAV Fixed Wing. The results are in the form of orthophoto aerial imagery with an area of 1577 hectares. The advantage of aerial photo maps is the real appearance of objects with high resolution. The village government can use this aerial photo map to determine village administrative boundaries, “rukun tetangga” and “rukun warga” boundaries, guidelines in making master plans as well as supporting data in determining village profiles.